Implementasi Pembelajaran Sentra Persiapan Pada Anak Kelompok Bermain Di Paud Terpadu Zaki's Club Gemolong Tahun Ajaran 2015/2016 - Apriani, Dewi, Drs. Ilham Sunaryo, M.Pd, AUD (2016)
The purpose of this research is to descripe of implementation of study of sentra preparation and know the factor supporting and pursuing implementation of study of sentra preparation at child of PlayGroup in Inwrought PAUD Zaki'S of Club of Stick of Gemolong Academic Year 2015/2016. Desain in this research that is descriptive. Data collecting in this research is by using methodinterview, observation, and documentation. Data analysed by using descriptive technique qualitative. Result of research: ( 1) Implementation of Study of Sentra Preparation in Inwrought PAUD Zaki'S Club Gemolong, consisted of three phases of activity that is Stepping Gift, Activity Play in Sentra Preparation, and Evaluate Study Sentra Preparation.Study of Sentra preparation in Inwrought PAUD Zaki'S of Club Gemolong have according a teacher obtain. however analyst of according to indicator of activitysentra preparation there is one which not yet according to that is indicator. ( 2) factor supporting and pursuing, factor supporting to cover the Headmaster Interest, Headmaster Role, densitas, interest of all, and teacher role. Factor pursuing for example Headmaster problems (teacher less own which creativity, altering teacher character), Teacher Problems (densitas bother the study process, curriculum, time management, and parent parent which less comprehend the study of sentra preparation).